891 EARLY EVOLUTION OF CARDIAC DAMAGE STAGING FOLLOWING TRANSCATHETER AORTIC VALVE REPLACEMENT: PREVALENCE, CLINICAL PATTERNS AND PROGNOSTIC SIGNIFICANCE. (15th December 2022) - Scudeler, Luca; Gallone, Guglielmo; Bruno, Francesco; Signorini, Antonio; Gorla, Riccardo; Melillo, Francesco; Tusa, Maurizio; Montorfano, Matteo; Leone, Pasquale; Cimaglia, Paolo; Pastore, Maria Concetta; Benfari, Giovanni; et al.
Abstract: Background: The early evolution of extravalvular cardiac damage following transcatheter aortic valve replacement (TAVR) as assessed by a previous validated score system remains unstudied. We sought to assess the patterns of early cardiac damage change among patients with severe aortic stenosis (AS) undergoing TAVR and its prognostic implications. Methods: The RECOVERY-TAVR is a multi-center, international retrospective registry including all consecutive patients undergoing TAVR in thirteen high-volume centers. All the enrolled patients with available paired echocardiography assessment pre- and post TAVR were included in this sub-analysis. Patients were categorized according to the extension of cardiac damage based on a previous published and validated classification (stage 0, no damage; stage 1, left ventricular damage; stage 2, left atrial or mitral valve damage; stage 3, pulmonary vasculature or tricuspid valve damage; and stage 4, right ventricular damage). The primary endpoint was a composite of all-cause mortality or first heart failure hospitalization at 1 year. The association of cardiac damage stage evaluated prior and following TAVR along with the staging evolution was assessed with multivariate Cox regression model (that include hemoglobin, NYHA class and max aortic valve gradient) for the primary outcome. Results: Of 1331 Patients included in the RECOVERY-TAVR registry with a full echocardiographic pre-TAVR assessment, 892 patients with available paired echocardiography exams were finally included in this analysis (pre-TAVR assessment: median 8 days prior to TAVR; post-TAVR assessment: median 7 days post-TAVR). 63 (7.1%) had stage 0/1, 433 (48.2%) had stage 2, 235 (26.3%) had stage 3 and 161 (18%) had stage 4 myocardial damage. Pre-TAVR myocardial damage staging was associated with the primary outcome (Adj-HR for myocardial stage increase: HR 1.40, 95% CI 1.01–1.93). Following TAVR 274 (30.7%) patients experienced myocardial damage improvement and 161 (18.1%) myocardial damage worsening. Post-TAVR myocardial damage staging was more strongly associated with the primary outcome (HR 1.55, 95%CI 1.14–2.10) as compared to pre-TAVR assessment. Male Sex (p = 0.044) and post-procedural permanent pacemaker implantation (p = 0.044) was associated with myocardial damage worsening, while the use of a balloon-expandable valve (p = 0.011) was associated with myocardial damage improvement. Early myocardial damage worsening (HR 1.89, 95%CI 1.12–3.21), but not early myocardial damage improvement (HR 0.86, 95%CI 0.54–1.37) was associated with the primary outcome. Conclusion: In patients undergoing TAVR, the extent of extravalvular cardiac damage prior to and early after TAVR has an independent prognostic value while early myocardial damage worsening following TAVR portends a poor prognosis. Whether strategies to improve procedural success and treatments addressing extravalvular myocardial damage early following TAVR may improve outcomes has to be prospectively assessed.